OTOMATISASI LINE KEMASAN Amunisi UNTUK MENINGKATKAN PROSES PRODUKSI Amunisi KALIBER KECIL (MU-5TJ) DI PT. PINDAD - Nugroho, Vicky Adhityo; George Royke Deksino; Yayat Ruyat; Muhamad Asvial; Rudi AG Gultom; Muhammad Taufiq Ramadhan (CV. AFDIFAL MAJU BERKAH, 2024)
Technology development in the defense industry is directed at building the ability to produce Alpalhankam that meets the operational requirements standardized by the Ministry of Defense, namely high quality, weather resistance, accuracy, combat power, high speed and difficult to detect. PT Pindad as a State-Owned Enterprise engaged in the Defense Industry is capable of making quality munitions, but the packaging line for small caliber munitions is still done manually. Therefore, it is necessary to automate the munition packaging line. In this research, the author conducted research using quantitative research methods through the Feasibility Study approach. The results and objectives of this study accelerate the packaging process on the small caliber munitions production line which was originally partly done semi-manually to use full machine automation and be able to support production so as to accelerate the fulfillment of small caliber munitions demand. The steps that are considered necessary are by investing in machines to increase the ability to package small caliber munitions and minimize the occurrence of errors in the munition packaging process